The explication of the social: Algorithms, drones and (counter-)terror. (September 2016) - Curtis, Neal
While drones are celebrated as the most precise form of weaponry that target specific individuals, this article argues that drone warfare still operates through the primary targeting of the environment. However, unlike earlier uses of bombs and rockets that targeted the physical environment, the drone apparatus – UAVs (Unmanned Aerial Vehicles), cameras, servers, algorithms – primarily targets the social environment of those being surveilled in order to decide who should be killed. Monitoring, profiling and projecting 'patterns of life' from everyday communication, association and movement is the primary function of the drone apparatus as it searches for 'signatures' of hostility among the mass of data it accumulates. The drone apparatus therefore functions by making explicit the background sayings and doings of the enemy's everyday life. To understand the nature of this explication of the social and its connection to contemporary warfare the article deploys the work of Peter Sloterdijk and his theory of 'atmoterrorism'.